The Effect of Meniran Herbs Extract (Phyllanthus niruri Linn) on The Histological Spectrum of The Uterus and Oviduct Rats (Rattus Norvegicus) - Rosa Mutianingsih; Khairil Pahmi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background The use of plants as natural medicinal ingredients isincreasingly in demand by the public because the plants are consideredto have lower negative effects than chemical drugs. The effect of mineranherbs extract (Phyllanthus niruri Linn) on the histological spectrum of theuterus and oviduct rat (Rattus Norvegicus) had been studied.Aim ofStudy Aim of this study to explore the effect of meniran herbs extract(Phyllanthus niruri Linn) on the histological spectrum of the uterus andoviduct rat (Rattus Norvegicus) Methods Wistar rats have been challengedwith 2% NaCl in drinking water to result in fibrotic uterus and oviduct.Phyllanthus niruri extract (200 mg/Kg) turned into given orally for 4weeks. Matrix extracellular abundance turned into decided via way ofmeans of HE Staining and measured via way of means of METAVIRFibrosis Score. The result of this examine have been assayed via way ofmeans of SPSS 16. Results P. niruri extract was potent to reduce thematrix extracellular in 2% NaCl-induced rats compared to control group(p<0.05) in uterus. Meanwhile, P. niruri extract was not able to decreasethe matrix extracellular in 2% NaCl-induced rats compared to controlgroup (p>0.05) in oviduct. Conclusion P. niruri extract was potent todecrease the matrix extracellular in the uterus of the rats, but in oviduct.